2018
DOI: 10.1016/j.cotox.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Environmental agents, oxidative stress and autoimmunity

Abstract: Oxidative stress (OS) plays an important role in the pathogenesis of a variety of autoimmune diseases (ADs) and many environmental agents participate in this process. Environmental agents, including trichloroethylene (TCE), silica, pristane, mercury, and smoke, are known to induce an autoimmune response, potentially through OS-mediated mechanisms. Here, we focus on unraveling the targets and signaling pathways that have been mechanistically linked with OS, as a result of exposure to these and numerous other en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…Environmental agent-mediated OS is pivotal in the pathogenesis of ADs and many such agents indeed participate through this mechanism. More in-depth studies to delineate the molecular and cellular pathways by which OS contributes to autoimmunity, especially the redox-immune interactions, ROS scavenger antioxidants, and exploring OS-mediated protein/DNA modifications in generating neoantigens, will provide critical information on OSmediated autoimmunity (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental agent-mediated OS is pivotal in the pathogenesis of ADs and many such agents indeed participate through this mechanism. More in-depth studies to delineate the molecular and cellular pathways by which OS contributes to autoimmunity, especially the redox-immune interactions, ROS scavenger antioxidants, and exploring OS-mediated protein/DNA modifications in generating neoantigens, will provide critical information on OSmediated autoimmunity (7).…”
Section: Discussionmentioning
confidence: 99%
“…The environmental factors account for up to 70% of all ADs (1,6). Strong evidence exists linking environmental agents, including solvents, crystalline silica, mercury, pesticides, pristine, and cigarette smoking with the development of various ADs (7). However, significant knowledge gaps remain regarding potential cellular, molecular, and immunological mechanisms by which environmental agents contribute to the disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds with antioxidant abilities have attracted the interest of researchers as well as pharmaceutical and food companies because they can offer human health benefits. The benefits include free radical scavenging capacity and interruption of oxidative processes, which can contribute to preventing human disease conditions (Khan & Wang, 2018). In addition to the interest in natural antioxidants, numerous research studies are being developed around the world seeking new antimicrobial agents derived from natural sources for applications in food products and in the formulation of new antibiotics (Saucedo-Pompa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…8-OHdG is one of the most widely recognized biomarkers of oxidative DNA damage (Cheah et al, 2017; Di Minno et al, 2016; Tatsch et al, 2015; Wu et al, 2005; Zhang et al, 2017). Previous studies have shown that TCE exposure enhances ROS generation and promotes oxidative stress, evidenced both in vivo and in vitro (Channel et al, 1998; Khan et al, 2001; Khan and Wang, 2018; Ogino et al, 1991; Wang et al, 2007, 2009, 2012; Zhu et al, 2005). To further evaluate the contribution of TCE-mediated oxidative stress in the induction/exacerbation of an autoimmune response, 8-OHdG formation in the livers of MRL+/+ mice exposed to TCE, NAC or TCE+NAC was quantitated.…”
Section: Resultsmentioning
confidence: 99%